Breathing time: a longue-durée multidisciplinary study of respiratory illnesses and airborne diseases in Switzerland (16th–21st century CE) - Tobias Hofstetter; Aude Fauvel; Silke Grabherr; Negahnaz Moghaddam (Homo)
This research is the first of its kind to assess of the impact of respiratory illnesses and airborne diseases (acronymized as “RIAD” hereafter) on Swiss mortality in the long run, between the 16th and the 21st century CE. It reviews historical, demographical, statistical, medical, and bioarchaeological, primary and secondary data originating from archive material or previously published specific analyses into the topic (n = 55). An innovative intersectional and multidisciplinary approach was developed in order to apprehend, collect, organize, and analyze data stemming from several different disciplinary fields. Through this approach, this research endeavors to answer the following questions: 1) what are the social and environmental factors guiding the risk or not of suffering from RIAD, 2) do these factors appear to be constant on a territorial scale and through time, 3) can the evolution of RIAD occurrences be correlated to the local history of a particular region? And 4) does a better understanding of RIAD dynamics in the past allow us to draw any useful lessons for their future sustainable management?Accordingly, collected raw data were converted and normalized into crude mortality, natality, and RIAD mortality rates per thousand individuals and subsequently set within the demographic and epidemiological transition model. This model serves as a relevant reading grid for the understanding of the pathological and demographic evolutions that this study highlights. Indeed, this data compilation effort enabled to reconstruct crude birth and death rates for Switzerland from 1580 CE to the present day and to present the latter in graphical form. This graphical presentation is a breakthrough in the field of RIAD research in Switzerland and further enabled to assess internal data coherence and trend evolutions by means of joinpoint regression analysis.Main results include the confirmation of the considerable impact of industrialization on the respiratory health of peri-alpine populations. They also underline the selective and versatile nature of the pressure exerted by respiratory diseases on specific socio-economic and demographic classes, whose composition has varied through time.This research was impeded by the uneven quality of the available sources. Nonetheless, it still provides a robust outlook on the longue-durée evolution of respiratory health. The obtained results might thus be of interest to a wide array of scholars active in the study of respiratory diseases through time, but also clinicians and health policy makers, as this study highlights particular aspect of the current health situation, and the future worldwide challenges posed notably by global urbanization, with regard to respiratory health issues.Future research could develop similar approaches in neighboring regions, or focus on specific types of RIAD, in order to contrast other local pathological signatures with the one presented in this manuscript.